2019
DOI: 10.12891/ceog4531.2019
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the endometrial thickness and estrogen level in athletes and sedentaries

Abstract: Background: The present study aims to examine the effect of estrogen level between volleyball player's and sedentary women' endometrial thickness with regular exercise. Materials and Methods: Seventeen athletes taking place in the 3 rd Turkish Women Volleyball League and 17 sedentary women participated in this study. The mean age of athletes was 20.70 ± 2.11 and sedentaries 21.70 ± 0.77 years has been identified. In the period between 10 and 11 days of their menstrual cycle, 2 cc venous blood was taken from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Bianco et al found that SB was a risk factor for PMS with a significantly higher prevalence of PMS in the sedentary group (54.1%) than in the exercise group (36.8%) [ 56 ]. A further study conducted in 2019 found that 42.5% of women in the exercise group felt pain during their menstrual cycle, compared to 60% in the sedentary group [ 57 ]. However, no significant differences were found between SB and PMS in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Bianco et al found that SB was a risk factor for PMS with a significantly higher prevalence of PMS in the sedentary group (54.1%) than in the exercise group (36.8%) [ 56 ]. A further study conducted in 2019 found that 42.5% of women in the exercise group felt pain during their menstrual cycle, compared to 60% in the sedentary group [ 57 ]. However, no significant differences were found between SB and PMS in our study.…”
Section: Discussionmentioning
confidence: 99%